Duration of equity overvaluation and managers' choice to use aggressive underlying earnings disclosure and accrual-based earnings management: Australian evidence. Issue 2 (August 2019) - Yang, Yiru; Abeysekera, Indra
Abstract: This paper examines whether equity overvaluation duration influences managers' choice of different earnings management mechanisms and how corporate governance and the Australian Securities and Investment Commission's underlying earnings disclosure guidelines influence managers' choices. The study samples Australian Securities Exchange 200 firms from 2009 to 2016. Findings show that on average, firms more likely engage in accrual-based earnings management in the early overvaluation stage. In later stages, firms more likely disclose underlying earnings aggressively to sustain overvaluation. Additionally, firms with a high proportion of independent directors on the board prefer to disclose underlying earnings aggressively to sustain the equity overvaluation; firms with a low proportion of independent directors prefer both accrual-based earnings management and aggressive underlying earnings disclosure to sustain the overvaluation. Moreover, firms that conform to the Commission's underlying earnings disclosure guidelines use neither accrual-based earnings management nor aggressive underlying earnings disclosure to sustain overvaluation, but non-conforming firms use both mechanisms.